2014
DOI: 10.9775/kvfd.2013.10550
|View full text |Cite
|
Sign up to set email alerts
|

Tereyağı Stabilitesi Üzerine Çörekotu (Nigella sativa L.) Uçucu Yağı Kullanılabilirliğinin Araştırılması

Abstract: The aim of this study was to investigate the effect of black cumin (Nigella sativa L.) essential oil on butter stability. For this aim, 0.05, 0.1 and 0.2 wt-% essential oil was added to the butter. Antioxidant activity of the essential oil was compared to that of synthetic antioxidant BHT (100 ppm). All samples were stored at 4±1ºC for 90 days. Thiobarbituric acid and peroxide values of all samples containing essential oil were decreased depending on concentrations. The amount of 0.2% of essential oil had show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
5
4
0
Order By: Relevance
“…The final product of oxidation of unsaturated fatty acids of malonaldehyde amount is identified with the TBA test to obtain information about the oxidation levels in butter . A study investigated the effect of nigella essential oil on butter stability and stated for all samples, containing the essential oil, TBA values reduce linked to concentration and adding 0.2% essential oil showed nearly equivalent power antioxidant activity to BHT . A research investigating the effect of beeswax extract on butter stability and a study identified similar results to the findings in our study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The final product of oxidation of unsaturated fatty acids of malonaldehyde amount is identified with the TBA test to obtain information about the oxidation levels in butter . A study investigated the effect of nigella essential oil on butter stability and stated for all samples, containing the essential oil, TBA values reduce linked to concentration and adding 0.2% essential oil showed nearly equivalent power antioxidant activity to BHT . A research investigating the effect of beeswax extract on butter stability and a study identified similar results to the findings in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Titratable acidity analysis titrates dissociated acidity and the non‐dissociated portion together . The data obtained in this research are in parallel with some research results …”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…But, some studies testify that addition of different spices and herbs or their extracts could improve storage stability of butter. Sage [5,7], rosemary [5,7], oregano [7], hazelnut [8], cinnamon [9], green tea [10], garlic [11], Satureja cilicica essential oil [12], black cumin essential oil [13] could extend butter stability and shelf-life due to antioxidative or antimicrobial activity. Polyphenolic compounds found in these plants significantly contribute to their protective activity.…”
Section: Introductionmentioning
confidence: 99%